Costless Capital Requirements - Raphael Flore (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Arguments for costs of capital requirements in the long run are based on trade-off theories of capital structure. This paper provides a critical assessment of these theories by studying how the optimal capital structure can be modified, when a firm uses the financial markets to alter its cash flow distribution. I show that, for any initial set of assets, the implementation of a certain fund structure allows the firm to reduce its leverage and its bankruptcy probability without a loss of value.
Keywords: G32; G30; G28; G10; 330